2015 International Conference and Workshops on Networked Systems (NetSys) 2015
DOI: 10.1109/netsys.2015.7089081
|View full text |Cite
|
Sign up to set email alerts
|

The potential of social-aware multimedia prefetching on mobile devices

Abstract: The access to Online Social Networks (OSN) and to media shared over these platforms account for around 20% of today's mobile Internet traffic. For mobile device users, the access to media content and specifically videos is still challenging and costly. Mobile contracts usually have a data cap and connection qualities can vary greatly, depending on the cellular network coverage. Prefetching mechanisms that fetch content items beforehand, in times when the mobile device is connected to a WiFi network, have a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…While it is easy to predict that a user will likely watch the next episode of a TV series on Netflix, for example, this does not hold in the case of music consumption. In fact, several studies have shown poor performance of approaches based on the user's subscription status and global item popularity [Koch et al 2017b;Wilk et al 2015Wilk et al , 2016.…”
Section: Improving Scalability and Efficiencymentioning
confidence: 99%
“…While it is easy to predict that a user will likely watch the next episode of a TV series on Netflix, for example, this does not hold in the case of music consumption. In fact, several studies have shown poor performance of approaches based on the user's subscription status and global item popularity [Koch et al 2017b;Wilk et al 2015Wilk et al , 2016.…”
Section: Improving Scalability and Efficiencymentioning
confidence: 99%